ANALISIS SEMANTIK PADA KATA SAFARA DAN DERIVASINYA DALAM AL-QUR’AN: STUDI ANALISIS MUSYTARAK LAFẒI - Fatimah, Gina Nur (Departemen Pendidikan Bahasa Arab, 2019)
The purpose of this study was to determine the concept of the word safara in the Qur'an based on semantic reviews, taking into account its derivation in the Qur'an. The word safara and its various forms are found six times in 11 verses and eight surahs. This study uses qualitative research, in the form of library research (library research) using semantic analysis methods to obtain a conclusion. The results of this study indicate that the basic meaning of safara is traveling. While the relational meaning syntagmatically has the meaning of travel, radiant, published, book and writer. However, paradigmatically safara has the same meaning with ẓahaba and raḥala.